STUDY OF ANTIBACTERIAL AND ANTIBIOFILM ACTIVITY AND MECHANISMS OF BIOSYNTHESIZED ZNO NANOPARTICLES - Juana, Tiffany
The use of antibiotics is an effective solution in overcoming infections caused by pathogenic bacteria. However, bacteria’s ability to form biofilm complicates their eradication. Nanoparticles has promising prospect in overcoming biofilms due to their antibacterial and antibiofilm activities. This research aims to examine the antibacterial and antibiofilm mechanism of ZnO nanoparticles synthesized by biological methods from Averrhoa bilimbi extract. The characterization of the crystallinity of ZnO nanoparticles indicates that the formed nanoparticles are of high purity. Morphology characterization reveals that the nanoparticles tend to have a spherical and hexagonal shape with a reduction in diameter size after calcination. The calcination process leads to nanoparticle deformation, size reduction, and recrystallization. Dynamic Light Scattering (DLS) characterization shows a low polydispersity index value, indicating a more homogeneous size distribution of ZnO nanoparticles. Surface compound characterization indicates that, after calcination, the nanoparticles lose organic groups and impurities with less discernible peaks. The antibacterial and antibiofilm properties of ZnO nanoparticles were tested against Escherichia coli at concentrations of 0, 25, 50, 100, 200, 400 mg/L before and after calcination. The increase in concentration of ZnO nanoparticles resulted in higher inhibition of microorganisms and biofilms, highest at 400 mg/L. Calcined ZnO nanoparticles exhibited higher antibacterial and antibiofilm mechanism. The dominant mechanism in antibiofilm activity of ZnO nanoparticles is the release of Zn2+ for noncalcined ZnO nanoparticles and production of reactive oxygen species (ROS) for calcined ZnO nanoparticles. The dominant mechanism in the antibiofilm activity of ZnO nanoparticles is associated with the presence of solid ZnO nanoparticles that can be internalized into the biofilm..